Characteristics of Light-Dependent Inorganic Carbon Uptake by Isolated Spinach Chloroplasts - Sicher, Richard C. (1984)
The light-dependent accumulation of radioactively labeled inorganic carbon in isolated spinach (Spinacia oleracea L.) chloroplasts was determined by silicone oil filtering centrifugation. Intact chloroplasts, dark-incubated 60 seconds at pH 7.6 and 23°C with 0.5 millimolar sodium bicarbonate, contained 0.5 to 1.0 millimolar internal inorganic carbon. The stromal pool of inorganic carbon increased 5- to 7-fold after 2 to 3 minutes of light. The saturated internal bicarbonate concentration of illuminated spinach chloroplasts was 10- to 20-fold greater than that of the external medium. This ratio decreased at lower temperatures and with increasing external bicarbonate. Over one-half the inorganic carbon found in intact spinach chloroplasts after 2 minutes of light was retained during a subsequent 3-minute dark incubation at 5°C. Calculations of light-induced stromal alkalization based on the uptake of radioactively labeled bicarbonate were 0.4 to 0.5 pH units less than measurements performed with [(14)C]dimethyloxazolidine-dione. About one-third of the binding sites on the enzyme ribulose 1,5-bisphosphate carboxylase were radiolabeled when the enzyme was activated in situ and (14)CO(2) bound to the activator site was trapped in the presence of carboxypentitol bisphosphates. Deleting orthophosphate from the incubation medium eliminated inorganic carbon accumulation in the stroma. Thus, bicarbonate ion distribution across the chloroplast envelope was not strictly pH dependent as predicted by the Henderson-Hasselbach formula. This finding is potentially explained by the presence of bound CO(2) in the chloroplast.